The Space in “Kisah Kota Kwon” A Short Story by Indra Tranggono - Fatmasari, Yuniar; Nurcholis, Akhmad (Metaphor, 2024)
This study is to find out the form of space presented in the short story written by Indra Tranggono entitled “Kisah Kota Kwon.” The study analyses the space, in this case is place and chaotic space to describe the opposition as inheritance of colonials. Although the short story has no direct relation with colonialism, yet by doing the study, the nation (colonial space) can be seen clearly. The method used in the study is descriptive qualitative. The results show that the place in the short story can be represented by the Kwon town, meanwhile the chaotic space can be seen from the journey taken by Molly as the representation of self conflict to the town itself.